ANALYSIS OF PRODUCTION COST MANAGEMENT AND PROFIT PLANNING TO SUPPORT THE SUSTAINABILITY OF ALD TOFU AGROINDUSTRY IN SIDOARJO - Septia Dwi Syaharani; Ika Sari Tondang; Taufik Setyadi (LPPM Universitas Malikussaleh - Indonesia, 2026)
Tofu agroindustry is one of the food-processing businesses that faces uncertainty in soybean raw material prices and sales fluctuations, which may affect business profitability. This study aims to analyze the application of Cost-Volume-Profit (CVP) analysis as a basis for profit planning at ALD Tofu Agroindustry in Sidoarjo. The research was conducted in April 2026 using a descriptive quantitative approach. Data were collected through interviews, observations, documentation, and literature review. CVP analysis was carried out by calculating the Contribution Margin (CM), Break-Even Point (BEP), Margin of Safety (MoS), Operating Leverage, and profit planning. The results indicate that the cost structure of ALD Tofu Agroindustry is dominated by variable costs, accounting for 92.8% of total production costs. The CVP analysis generated a contribution margin ratio of 21.03%, a break-even point of 5,714 molds, and a relatively high margin of safety. To achieve a target profit of 25% of sales, the company needs to increase its sales volume to 29,084 molds. These findings demonstrate that CVP analysis can serve as a basis for decision-making in profit planning and the sustainability of ALD Tofu Agroindustry in Sidoarjo.Keywords: Cost-Volume-Profit Analysis, Profit Planning, Tofu Agroindustry, Business Sustainability.